Who wins olympic bids? - Wolfgang Maennig; Christopher Vierhaus (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2014)
The prospect of hosting the Olympic Games is attractive to many cities around the world. This article examines 147 variables' potential to discriminate successful from unsuccessful Olympic bids. Our stepwise, rank-ordered logistic regression model includes nine determinants supporting the contention that economic, political and sports/Olympic factors are important. Hosts are characterized by larger markets and higher medium-term growth economies. Olympic bids that follow a political liberalization are rewarded with additional votes. Moreover, cities offering winning bids are more experienced at hosting and have no dispute with the International Olympic Committee (IOC). IOC members disfavor bids lacking a sufficient number of existing stadiums and bidding cities of fewer than 2.5 million inhabitants. Finally, we observe "it is the country's turn" election behavior - countries that have not hosted the Olympics for a long period are favored.
Keywords: 330; Olympic Summer Games; mega events; indicators; host election; bidding process; IOC